Adoption of herbicide resistance tests in German arable farming: Insights from the theory of planned behaviour - Marius Michels; Vanessa Bonke; Oliver Musshoff (Australian Journal of Agricultural and Resource Economics, 2024)
An increasing number of herbicide-resistant weeds challenge farming systems worldwide. Bans on active ingredients in chemical crop protection, which result in fewer weed control options, emphasise the importance of herbicide resistance management in arable farming. Resistance testing allows farmers to get an objective overview of the prevailing herbicide resistances on their land and to adjust their management strategies accordingly. Nevertheless, no study has examined farmers' adoption of herbicide resistance tests. For this purpose, an online survey with 197 German arable farmers was conducted. The adoption decision was investigated by applying the theory of planned behaviour framework. The results suggest that informing farmers of the economic benefits associated with herbicide resistance tests can facilitate widespread adoption. Furthermore, awareness of the availability of herbicide resistance tests needs to be raised through both advertising and crop consultants. Results from this study are relevant for several interest groups as the usage of herbicide resistance tests can help reduce the emergence of new resistance by optimising herbicide use at the farm level.
Keywords: 330; herbicide resistance management; herbicide resistance test; partial least squares structural equation modelling; theory of planned behaviour; weed management